The contribution of the Asante Kings to the growth of Methodism in Asante: 1839-2002 - Antwi, Moses Very Rev. (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Philosophy in Religious Studies, 2011